Development And Analysis Of An Inverse Microwave Scattering Model For Active Remote Sensing Of Sea Ice - Lee, Yu Jen (2009)
In this study, an inverse microwave scattering model for sea ice has been developed for the purpose of sea ice thickness retrieval using radar backscatter data. The model is loosely based on the Radiative-Transfer-Thermodynamic Inverse Model for Sea Ice Thickness Retrieval from Time-Series Scattering Data.